Odontogenic infection causing orbital cellulitis in a pediatric patient - De Assis-Costa, Marcelo Dias Moreira; Santos, George Soares; Maciel, Jucileia [UNESP]; Sonoda, Celso Koogi [UNESP]; De Melo, Willian Morais [UNESP] (Wolters Kluwer, 2013)
Odontogenic abscess can become an orbital cellulitis, causing potentially serious intracranial and orbital complications. The full clinical complications from odontogenic orbital cellulitis in a pediatric patient are rarely seen daily in hospital emergency departments. Thus, odontogenic orbital cellulitis still remains a rarity, resulting in a medical challenge. With this in mind, this study aimed to describe a case of periorbital and orbital cellulitis resulting from odontogenic origin in a 6-year-old patient who was successfully treated by performing intravenous antibiotic administration combined with surgical drainage. Copyright © 2013 by Mutaz B. Habal, MD.
Keywords: Odontogenic infection; Orbit; Orbital cellulitis; Surgical management